2013
DOI: 10.1200/jco.2013.31.15_suppl.7113
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for selective benefit of sequential treatment with azanucleosides in patients with myelodysplastic syndromes (MDS).

Abstract: 7113 Background: Azanucleosides (AZN) remain the mainstay of therapy in myelodysplastic syndrome (MDS). Sequential use of AZNs is common practice given the limited alternatives. The only published experience described 14 patients showing a 28% response with decitabine (DAC) after failure or lack of response to azacitidine (AZA). To investigate the potential benefit of this approach,we reviewed cases of sequential AZN treatment. Methods: Patients who received treatment with both AZNs were identified through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Response rates to decitabine after azacitidine are ,30%, [59][60][61] and only 1 study reported a response rate of 40% for patients who received azacitidine after first-line decitabine. 60 Because of the slightly different mechanisms of action of the 2 agents, switching may be partially justified, but recent evidence 33 suggests that azacitidine is clinically active only when incorporated into DNA, with a mechanism overlapping that of decitabine. In any case, the prolonged duration of HMA treatment seems to account for the increased responses observed when the second HMA is sequentially introduced.…”
Section: Management Of Hma Failuresmentioning
confidence: 99%
“…Response rates to decitabine after azacitidine are ,30%, [59][60][61] and only 1 study reported a response rate of 40% for patients who received azacitidine after first-line decitabine. 60 Because of the slightly different mechanisms of action of the 2 agents, switching may be partially justified, but recent evidence 33 suggests that azacitidine is clinically active only when incorporated into DNA, with a mechanism overlapping that of decitabine. In any case, the prolonged duration of HMA treatment seems to account for the increased responses observed when the second HMA is sequentially introduced.…”
Section: Management Of Hma Failuresmentioning
confidence: 99%